Komunikasi Efektif Sebagai Upaya Penanggulangan Bencana Alam di Kota Padangsidimpuan - Sigit Hardiyanto; Darmansyah Pulungan (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
Natural disasters is a natural events that results in a big impact for of human populations .The city padangsidimpuan hit by natural disaster flooding due to heavy rain has made the rivers to overflow and as a result sweeping stems ayumi houses on the outskirts of rivers and result in casualties died .Regional disaster management agency ( bpbd ) padangsidimpuan city is one of the most important factors in make a difference to the society about preparedness to natural disasters in their areas .Of the study which used in this case study qualitative wear with the approach .The source of information in this review are personnel ( bpbd ) and city people padangsidimpuan .The results indicate communication verbal effective both effective and non verbal effective need to and must be intense will not cease to be done to make the processes of communication that is konatif can work well. Expected bpbd city padangsidimpuan and the community communicating intense that they know will things grows about about natural disasters and preserving environment not make waste to rivers and not cutting trees illegally loging .